A simplified microwave-based motion detector for home cage activity monitoring in mice - Genewsky, Andreas; Heinz, Daniel E. (Medical engineering & physics, 2017)
Locomotor activity of rodents is an important readout to assess well-being and physical health, and is pivotal for behavioral phenotyping. Measuring homecage-activity with standard and cost-effective optical methods in mice has become difficult, as modern housing conditions (e.g. individually ventilated cages, cage enrichment) do not allow constant, unobstructed, visual access. Resolving this issue either makes greater investments necessary, especially if several experiments will be run in parallel, or is at the animals’ expense. The purpose of this study is to provide an easy, yet satisfying solution for the behavioral biologist at novice makers level.
Gesehen am 03.05.2018